Comparison of Offenders with Early- and Late-Starting Antisocial Behavior in Colombia - Klevens, Joanne; Restrepo, Ofelia; Roca, Juanita; Martinez, Adriana (International journal of offender therapy and comparative criminology, 2000)
A sample of 223 detained offenders in five cities in Colombia, South America, were divided according to childhood or adolescent onset of antisocial behavior and compared on type of offense, characteristics of family of origin, and personal history. No significant differences were found as to type of offense committed between these two groups, but individuals with childhood onset of antisocial behavior were more likely to report multiple problem behavior at all ages, family antecedents of delinquency and alcohol abuse, greater exposure to family life changes, psychological abuse, severe childhood punishments, and lower self-esteem and sense of coherence as compared to individuals first manifesting antisocial behavior after adolescence. These differences were independent of mother's level of education, head of the household's occupational level, and family size. The results add evidence from a different social and cultural context as to the heterogeneity among offenders related to the age of onset of antisocial behavior